DESIGN AND RESEARCH OF A DUAL-BAND IR LENS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Infrared imaging systems are widely used in military and civilian applications. Acquiring IR images simultaneously in two spectral ranges provides additional and more detailed information about objects. Dual band IR systems are equipped with a lens that operates simultaneously in two ranges of the IR spectrum MWIR and LWIR. In the design of such a lens, a problem arises with the strong dependence of the refractive index on the wavelength, which requires the correction of chromatic aberration simultaneously in two spectral ranges. In this article, the possibilities for the synthesis of dual-band lenses in the MWIR and LWIR spectrum using different optical materials are analyzed. The possible combinations of such materials are determined. Dual band lenses are designed using different material combinations. Their optical characteristics are investigated and the possibility of creating relatively simple high-quality dual-band IR lenses is shown.